Olympism and Human Rights A Critical Analysis Comparing Different National Olympic Education Programmes in Europe - Lang Fuentes, Rebekka (Wiesbaden : Springer Fachmedien Wiesbaden : Imprint: Springer VS, 2022)
Olympic Education is tasked by both Olympism (Olympic Movement's underlying philosophy) and the United Nations to educate on human rights. This study explores how present this call is in contemporary European Olympic Education. National Olympic Education programmes from twelve countries are examined and compared: Armenia, Austria, Belarus, Croatia, Hungary, Israel, Germany, Lithuania, Portugal, Russia, Slovenia, and Spain. Responses by individuals with NOAs' leadership positions to a semi-standardized research questionnaire as well as written information by NOAs on implemented national Olympic Education programmes, collected during February-May 2021, are subjected to a content analysis. Results indicate that human rights are explicitly and implicitly included as an educational theme in contemporary Olympic Education programmes. Parallels between human rights education and Olympic Education can be drawn. About the author Rebekka Lang Fuentes studied B.A. Sport and Sports Science in Mainz. She received a scholarship from the European Commission for the international studies M.A. Sports Ethics and Integrity, an Erasmus Mundus Joint Master Degree at six universities on the European continent. .
Olympism -- Human Rights -- Human Rights and Olympism -- Conclusion of Theoretical Background -- Research Method -- Results -- Discussion.
Keywords: Human rights; Sports sciences; Physical education and training; Sports-Sociological aspects; Human Rights; Sport Analytics; Sport Education and Didactics; Sport Sociology